Systematic review and meta-analysis for prevention of cardiovascular complications using GLP-1 receptor agonists and SGLT-2 inhibitors in obese diabetic patients - Kazushi Uneda (Nature Portfolio, 2021)
Abstract Patients with type 2 diabetes mellitus (T2DM) and obesity are at high risk of developing cardiovascular disease (CVD). Both glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and sodium-glucose cotransporter (SGLT-2) inhibitors have been shown to prevent CVD in T2DM patients. Additionally, the two drugs reduce body mass. However, it is unknown which drug is more effective at reducing the risk of CVD in such patients. We searched Medline, EMBASE, and Cochrane Library records to February 20, 2021 and performed a network meta-analysis to compare the efficacy with which the drugs reduced the risk of major adverse cardiovascular events (MACE). We included 102,728 patients in 12 studies containing data of obesity subgroup analyses. In T2DM patients with obesity, GLP-1 RAs significantly reduced the risk of MACE versus placebo (relative risk, RR [95% confidence interval, CI]: 0.88 [0.81–0.96]), whereas SGLT-2 inhibitors showed a tendency (RR [95% CI]: 0.91 [0.83–1.00]). In an indirect comparison, GLP-1 RAs were not associated with a significant difference in MACE compared with SGLT-2 inhibitors (RR [95% CI]: 0.97 [0.85–1.09]). Thus, GLP-1 RAs are effective at preventing MACE than placebo in T2DM patients with obesity, although further studies are warranted to conclude their superiority to SGLT-2 inhibitors.